2021
DOI: 10.3390/land10050505
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne Estimation of Leaf Area Index in Cotton, Tomato, and Wheat Using Sentinel-2

Abstract: Satellite remote sensing is a useful tool for estimating crop variables, particularly Leaf Area Index (LAI), which plays a pivotal role in monitoring crop development. The goal of this study was to identify the optimal Sentinel-2 bands for LAI estimation and to derive Vegetation Indices (VI) that are well correlated with LAI. Linear regression models between time series of Sentinel-2 imagery and field-measured LAI showed that Sentinel-2 Band-8A—Narrow Near InfraRed (NIR) is more accurate for LAI estimation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
(62 reference statements)
0
8
1
Order By: Relevance
“…In this study, this coefficient of determination was 0.45 for field measurements and 0.35 for PROSAIL simulation, which are within the variation of previous reports. However, we found EVI to produce R 2 = 0.26 and 0.27 with LAI for field measurements and model simulations in our study, respectively, lower than the average value (R 2 = 0.66) of the three species (tomato, cotton and wheat) reported by Kaplan et al [64]. Again, this can be attributed to the larger variation in MTA and partly attributed to soil spectral properties used in the current study.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In this study, this coefficient of determination was 0.45 for field measurements and 0.35 for PROSAIL simulation, which are within the variation of previous reports. However, we found EVI to produce R 2 = 0.26 and 0.27 with LAI for field measurements and model simulations in our study, respectively, lower than the average value (R 2 = 0.66) of the three species (tomato, cotton and wheat) reported by Kaplan et al [64]. Again, this can be attributed to the larger variation in MTA and partly attributed to soil spectral properties used in the current study.…”
Section: Discussioncontrasting
confidence: 91%
“…Leaf inclination angle had large effects on red NIR-based vegetation indices for LAI or leaf chlorophyll content estimation [65][66][67]. The statistical relationships between LAI and S2 VIs for single species have been assessed in previous studies, and the R 2 for NDVI has been found to differ largely between wheat, maize and alfalfa (R 2 = 0.14-0.72) [68], and between tomato, cotton and wheat (R 2 = 0.05-0.83) [64]. In this study, this coefficient of determination was 0.45 for field measurements and 0.35 for PROSAIL simulation, which are within the variation of previous reports.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The LAI data for potato, corn and cotton were interpolated from 6, 12, and 9 data points, respectively, which were graphically generated based on previous studies (Bufon et al, 2011;Liu et al, 2002;Monteiro et al, 2006;Villa et al, 2017). The interpolated LAI data were then adjusted (rescaled) according to local studies (Gitelson et al, 2003;Kaplan & Rozenstein, 2021;Nguy-Robertson et al, 2014). All of the irrigation, LAI, and meteorological data that we used are available in the Data Set S1 in Supporting Information S1 and in Weissman et al (2022).…”
Section: Modeling Setupmentioning
confidence: 99%
“…Four main classes of retrieval techniques from optical remotely sensed images have been used for LAI estimations over the years (Verrelst et al, 2019). Parametric regression methods rely on the explicit relationships between LAI and vegetation indices (VIs) (Ali et al, 2015;Brogi et al, 2020;Kaplan & Rozenstein, 2021;Xing et al, 2020). Linear and nonlinear nonparametric regression methods, e.g., Gaussian Process Regression (Rivera-Caicedo et al, 2017), artificial neural networks (Chen et al, 2020), random forests (Abdelbaki et al, 2021), and support vector machines (Tuia et al, 2011;Zhang et al, 2021), do not assume any explicit relationship between LAI and spectral reflectance.…”
Section: Introductionmentioning
confidence: 99%